Chemical Variation and Potential of Kaempferia Oils as Larvicide Against Aedes aegypti - Jukreera Panyakaew (2018)
© 2017 Har Krishan Bhalla & Sons. The essential oil constituents of the Kaempferia species, specifically K. angustiflora, K. marginata and the three varieties of K. galanga, i.e., K. galanga 1, K. galanga 2 and K. galanga 3 from Chiang Mai Province, Thailand, were studied using gas chromatography-mass spectrometry (GC-MS). Monoterpene hydrocarbons and cinnamate derivatives were identified as the phytochemical markers of these Kaempferia species. The chemical variation of these oils was investigated using Principle Component Analysis (PCA). Cinnamate derivatives were found to be the main components in the three varieties of K. galanga, whereas K. marginata and K. angustiflora consisted of monoterpene hydrocarbons. Comparing the chemical variation between Kaempferia species in this research and other areas in previous reports revealed similar constituents in different quantities. Additionally, the three varieties of K. galanga showed significant larvicidal activity, with LC50values ranging from 49.03 to 53.48 μg/ml. Based on partial least squares (PLS) regression, δ-3-carene, E-ethyl cinnamate, ethyl-p-methoxycinnamate, γ-cadinene and n-pentadecane are the dominant compounds and contributed positively to the larvicidal activity.